Six Children’s Books by Theodor “Dr. Seuss” Geisel - Alderman, Alaynna M. (2024)
This paper primarily focuses on Dr. Seuss Enterprises’ decision to cease publication of six children’s books on March 2, 2021, for illustrations that have been deemed racist and politically incorrect towards the Asian, Inuit, and African communities. The company did not specify which illustrations were racist but announced the six books—And to Think That I Saw It on Mulberry Street (1937), McElligot’s Pool (1947), If I Ran The Zoo (1950), Scrambled Eggs Super! (1953), On Beyond Zebra! (1955), and The Cat’s Quizzer (1976)—to “portray people in ways that are hurtful and wrong.” The research conducted adds to the scholarly conversation of the impacts a dual audience can have in children’s literature. As attention to inclusivity has grown in Western culture, this study targets a very relevant and recent event. Using primarily qualitative with some quantitative research, this paper contributes to growing questions of what is “good” versus “bad” representation, is revision or censorship intended for children or adults, and is ceasing publication a form of censorship? The chapters provide a chronological review o events between 2017 and 2021; analyses on the six books; assessment of the dual audience and of adult curation of children’s books; and discussion on authorial intention and recognition of the third audience. This study finds that the dual audience dynamic in children's literature encourages an impulse to revise or censor on behalf of children whose own perceptions and power are hard to assess. But the third audience vantage point discourages such revisions and omissions because they limit the scope of and access to worlds of ideas.